Modelling, simulation and analysis of high step up DC-DC converter using coupled inductor and voltage multiplier cell using PSCAD. (2nd January 2020) - Das, P. Vipin; Karuppanan, P.; Singh, Asheesh Kumar; Chitti Babu, B.
ABSTRACT: This paper propose a high gain non-isolated DC-DC converter using coupled inductor at input stage and capacitor voltage multiplier cell (VMC) at the output stage. The input coupled inductor is responsible for ripple reduction and the output capacitor multiplier cells are intended to improve the voltage gain. The use of VMC reduces the voltage stress across the power converter switches and facilitates to exploit low rated switches. It will reduce the conduction, switching losses and improve the converter efficiency. The charge balance between the blocking capacitor helps to achieve uniform current sharing in each phase of interleaving operation. The projected DC-DC converter is highly recommended for fuel cell application due to the low input current ripple and high gain. The mathematical model and simulation analysis has been conducted in detailed to validate the converter topology. The converter characteristics have been compared with the high conversion ratio DC-DC converter.